Correlation of colposcopy with biopsy in cases of abnormal cervical cytology - Subedi, Kirtipal (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: This study aims to find out the role of colposcopy and its correlation with cervical biopsy in detection of pre malignant cervical lesion. Methodology: This is hospital based prospective observational study on 60 cases with abnormal cervical cytology reports conducted in the Department of Obstetrics and Gynecology, PMWH, Thapathali, Kathmandu. Colposcopy guided biopsies were done and findings noted. Results: Among 60 cases enrolled in the study the most common cervical cytology finding was ASCUS, LSIL, HSIL and ASC-H present in 46.6%, 31.6%, 15% and 6.6% respectively. The colposcopy finding among these cases was normal, CIN1, CIN 2 and CIN 3 in 45%, 23.3%, 16.7% and 9% respectively. Among these cases the most common biopsy finding was normal, CIN 1, CIN 2, CIN 3 and squamous cell carcinoma in 55%, 18.3%, 8.3%, 15% and 3.3% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of colposcopy with CIN 1 as disease threshold was calculated to be 80.6%, 93.1%, 81.8% and 92.6% respectively. While evaluating the validity of colposcopy with histopathology, colposcopy seems to make an accurate diagnosis in 75% of cases, overestimating in 15% and underestimating in 8% of cases. Conclusions: There is a good correlation of colposcopy with histopathological diagnosis of cervical cancer. Keywords: colposcopy, cytology, diagnosis, premalignant